Digital Graveyards: A study about data visualization portraying death during the COVID-19 pandemic - Ugaya Mazza, Larissa; Fadel, Luciane Maria (InfoDesign, 2023)
Data visualizations have been widely used during the COVID-19 pandemic, serving as a source of information about the disease or helping researchers establish patterns and make predictions. However, data visualizations carry many hidden messages, and it is up to the designer to use visual elements wisely in order to foster a healthy interaction. When it comes to death, information becomes delicate, and it is important to consider the connections between form and meaning, as these can influence audience behavior. Seeking to better understand how data visualizations have dealt with such a topic, this article analyzes two data visualizations on the number of deaths by COVID-19 through the analytical lens of remediation. The Close Reading method was applied to map the elements of both visualizations and analyze how these can promote death awareness.